2013
DOI: 10.1016/j.powtec.2013.05.046
|View full text |Cite
|
Sign up to set email alerts
|

A novel catalytic method for the synthesis of spherical aragonite nanoparticles from cockle shells

Abstract: For the first time, we report here a novel top down catalytic approach for the synthesis of aragonite nanoparticles with spherical morphology from cockleshells. Cockle shell is a natural reservoir of aragonite which is a biogenic polymorph of calcium carbonate. Aragonite polymorph is widely used in the repair of fractured bone, development of advanced drug delivery systems, and tissue scaffolds. The method involves an easily performable and lowcost mechanical stirring of the micron-sized cockle shell powders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 13 publications
5
21
0
Order By: Relevance
“…11 The crystallinity phases of the samples were determined using diffraction angles from 5° to 70°, and the experiment was conducted at 37°C.…”
Section: Physicochemical Characterization Of Vanp Crystallinity and Cmentioning
confidence: 99%
See 3 more Smart Citations
“…11 The crystallinity phases of the samples were determined using diffraction angles from 5° to 70°, and the experiment was conducted at 37°C.…”
Section: Physicochemical Characterization Of Vanp Crystallinity and Cmentioning
confidence: 99%
“…All the diffraction spectra of the nanoparticles conform with the reference spectra (JCPDS file no 00-041-1475) for aragonite polymorph of calcium carbonate. 11 The high intensity of the peaks was attributed to the high crystallinity of the nanoparticles. The XRD patterns of VANP were very much similar to the naked nanoparticles; thus, we concluded that the crystallinity of the ANP was maintained after loading with vancomycin.…”
Section: X-ray Powder Diffraction Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a case in point, an eco-friendly and large-scale approach was applied to prepare high purity CaCO 3 , in which the mollusk shell was calcined in the propane atmosphere to remove the organic matters (Barros et al, 2009). Islam et al (2013aIslam et al ( , 2013b described a catalytic method for the synthesis of aragonite nanoparticles from cockle shells, where dodecyldimethyl betaine was used as a biomineralization catalyst. Hydroxy-apatite powders applicable in the bone tissue engineering could also be prepared from shell wastes (Wu et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%